(untitled) (diségno, 2021)
How was architecture designed in the 1930s? This is the starting question through which we want to set up a wider reflection on the architecture of that period, taking as reference a Sicilian project by Luigi Moretti: the Casa del Balilla in Messina, dating back to 1936. The initial analysis of the building’s drawings is aimed at evaluating the expressive contents of drawing as a disciplinary instrument of architecture. But the fact that Luigi Moretti’s first work in Sicily has never been built has also led to the elaboration of a further exegesis, consisting in the construction of a virtual three-dimensional model of the building: a process aimed at verifying the complexity of the forms transcending the unpredictability that pervades the final product of this logical-applicative consecutio of the tools of Science of Representation, digital images. Therefore, the reduction of the three-dimensional object (the model) into a two-dimensional entity (the image) poses both metalinguistic and projective questions: the model acts as a critical instrument that explains the reality imagined by Luigi Moretti, returning – through the heuristic force of images – all those syntactic, spatial, architectural, urban or even territorial tensions that the building would have possibly generated.